The role of fintech in improving financial literacy in micro, small and medium enterprises in Subang - Fahmiyatu Rizqiya; Enjang Suherman; Dwi Epty Hidayaty (International Journal of Applied Finance and Business Studies, 2022)
This study aims to analyze the role of financial technology in UMKM in Subang to improve financial literacy. In this study, researchers took three samples at random, from Subang Regency and Subang City. Analysis of the data used in this study is to use data reduction data and then the presentation of the data and the last is drawing conclusions. The results of the study showed that the four informants as a whole accepted the presence of fintech because fintech could assist UMKM actors in providing convenience and efficiency in terms of technology-based financial management, including digitizing financial reports, payment technology and online loans. However, of all the roles of fintech, UMKM actors in this study did not fully know what the role of fintech was because of the lack of socialization about fintech in UMKM. Most UMKM actors still choose to pay for business capital, many still choose banks because banks are trusted and there are legal institutions that regulate them. Of the four UMKM actors, the impact after using fintech is more positive or the many benefits obtained after registering for fintech for their business, the more efficient and effective business activities are, which makes the implementation of fintech and the development of the times to demand business people to use fintech which has many advantages to improve literacy. finance for UMKM.